1994
DOI: 10.1111/j.1365-2591.1994.tb00274.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sodium hypochlorite on the permeability and structure of cervical human dentine

Abstract: The effect of 5% sodium hypochlorite and 35% hydrogen peroxide on dentine samples in vitro was investigated. It was demonstrated that both 5% NaOCl and 35% H2O2 depletes the dentine, which can be recorded as weight loss. Sodium hypochlorite removes approximately 14% of dry weight from dentine samples in 24 h; hydrogen peroxide is half as destructive. The hydraulic conductance (Lp) of dentine after treatment with NaOCl is increased over 100%. It is suggested that the use of high concentrations of sodium hypochl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
34
0
11

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 16 publications
2
34
0
11
Order By: Relevance
“…Similar observations were made in dentine by Barbosa et al [1994], Inaba et al [1995], and Sakae et al [1988]. It was also reported by Barbosa et al [1994] that the treatment of calcified tissues with sodium hypochlorite caused some mineral besides organic materials to dissolve. With regard to these, sodium hypochlorite treatment would undoubtedly enhance the diffusion of inorganic materials through enamel [Robinson et al, 1990] thereby influencing the rate of development and progression of demineralisation.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Similar observations were made in dentine by Barbosa et al [1994], Inaba et al [1995], and Sakae et al [1988]. It was also reported by Barbosa et al [1994] that the treatment of calcified tissues with sodium hypochlorite caused some mineral besides organic materials to dissolve. With regard to these, sodium hypochlorite treatment would undoubtedly enhance the diffusion of inorganic materials through enamel [Robinson et al, 1990] thereby influencing the rate of development and progression of demineralisation.…”
Section: Discussionsupporting
confidence: 73%
“…Sodium hypochlorite treatment of enamel resulted in increased permeability and surface alterations [Bitter, 1992] consequent to removal of organic materials by deproteinisation [Robinson et al, 1990]. Similar observations were made in dentine by Barbosa et al [1994], Inaba et al [1995], and Sakae et al [1988]. It was also reported by Barbosa et al [1994] that the treatment of calcified tissues with sodium hypochlorite caused some mineral besides organic materials to dissolve.…”
Section: Discussionsupporting
confidence: 67%
“…Previous observations and preliminary studies in our laboratory indicated that NaOCl also has a considerable capacity to disintegrate carious dentin when applied in a large excess [Nordbø et al, 1996]. Calcified dentin, on the other hand, does not seem to be significantly altered by NaOCl [Rosenfeld et al, 1978], al-though this perception has recently been called into question [Barbosa et al, 1994;Inaba et al, 1995]. The commercially available product Carisolv™ (MediTeam AB, Gothenburgh, Sweden) [Ericson et al, 1999], which is based on an NaOCl-containing solution and represents a further development of the former American product Caridex™, has the capacity to soften carious dentin.…”
mentioning
confidence: 72%
“…Para observar a ação do hipoclorito de sódio sobre a limpeza, anti-sepsia, dissolução tecidual e o aumento de permeabilidade dentinária, dentro do endoductodôncio, bem como sua biocompatibilidade, inúmeros trabalhos foram realizados e dentre eles podem citar-se: MARSHALL (1960), STEWART et al (1969), SHIH et al (1970), SENIA et al (1971), ROBAZZA (1973), NERY et al (1982), MARTIN & SPRING (1975), McCOMB & SMITH (1976), TREPAGNER et al (1977), HAND et al (1978), CUNNINGHAM & BALEKJIAN (1980), WENNBERG (1980), CUNNINGHAN & JOSEPH (1980), ABOU-RASS & PICCININO (1982), MOORER & WESSELING (1982), PÉCORA (1985), FOGEL & PASHLEY (1990), CHEUNG & STOCK (1993), SAVIOLI et al (1993), BARBOSA et al (1994), PEREZ et al (1996) e PÉCORA et al (1999.…”
Section: Introductionunclassified